Mengasah Kemampuan Bahasa Anak Usia Dini: Inovasi Metode Bercerita dengan Media Visual - Lisdiyana, Lisdiyana (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
Early childhood language skills are an important aspect of development that plays a role in the process of communication, learning, and socialization. However, based on initial observations at Raudhatul Athfal Nurul Islam Seresam, there are still many children aged 5-6 years who have difficulty in listening and speaking, such as limited vocabulary, unclear pronunciation, and low participation in communication. This study aims to determine the implementation of the storytelling method through visual media and its impact on improving early childhood language skills in the aspects of listening and speaking. The research method used is the Classroom Action Research (CAR) model of Kemmis and McTaggart which was carried out in two cycles. The subjects of the study consisted of 18 students in group B at Raudhatul Athfal Nurul Islam Seresam. Data collection techniques include observation, interviews, and documentation, then analyzed descriptively quantitatively and qualitatively. The results of the study showed that the application of the storytelling method through visual media was able to improve children's language skills. The percentage of development achievement increased from 39% in the pre-cycle to 60% at the end of Cycle I, and reached 85% at the end of Cycle II. This shows that the storytelling method with the support of visual media is effective in strengthening children's listening and speaking skills. Thus, it can be concluded that the storytelling method through visual media can be implemented as a strategy in learning to improve the language skills of early childhood, and is able to create a fun and communicative learning atmosphere.